Modativismo: When fashion meets the struggle (Revista de Ensino em Artes, Moda e Design, 2026)
This review analyzes the book Modativism: When Fashion Meets the Struggle, by Carol Barreto, published by Editora Paralela in 2024. The work offers a reflection on the relationships between fashion, body, and politics, establishing the concept of “modativism” as an epistemology of resistance and a project of aesthetic reexistence for Black women. Barreto conceives fashion as a territory of symbolic and pedagogical struggle, in which the act of dressing becomes a political and spiritual gesture. Academic whiteness and the Eurocentric paradigms that structure fashion teaching and practice are questioned by the author through the proposal of a decolonial pedagogy grounded in ancestry, collectivity, and creation as a form of thought. By integrating art, activism, and education, Modativism stands as a fundamental work for understanding fashion as a critical practice and a field of emancipation.
Keywords: fashion; ancestrality; decoloniality; blackness